Improving forest benefits for the poor: learning from community-based forest enterprises in Nepal - Pandit, B.H.; Albano, A.; Kumar, C. (Center for International Forestry Research, 2008)
The study documents practices of 28 community-based forest enterprises (CBFEs) in Nepal, representing different enterprise models - FUGs (CFUGs or LFUGs), networks, cooperatives, and companies. FUGs are primarily constrained by their limited scale in terms of membership and land area. The formation of intergroups and networks minimizes this limitation. Networks are often constrained from doing group enterprises since they do not have legal identity to transact as a group and this constraint can be overcome by registering as a formal business entity - either as a cooperative or a company. Specific constraints to cooperatives and companies were also identified and the effective practices presented. The study highlighted many constraints to enterprise development targeting to include and benefit the poorest of the poor. One good practice is the provision of a revolving fund by donors that will enable the poor to buy shares in the cooperative or company. Other practices include offering labour opportunities to the poorest (e.g. NTFP collection and factory labour), and representation of the poorest and marginalized in FUG executive committees. Recommendations include replicating the good practices of the CBFEs while improving on their weaknesses such as federating and formalizing FUGs into networks, cooperatives, or private companies; adding value to variation forest products; increasing equity in distribution of benefits; promoting resource sustainability; and the capacity building of the various stakeholders.